Kajian Teoritis Perbandingan Kurikulum IPS di Indonesia dan Amerika - I Ketut Suparya (Edukasi: Jurnal Pendidikan Dasar, 2022)
The purpose of writing this article is to compare the social studies curriculum developed in Indonesia with that of the United States. The analysis focused on the history of development, the material taught and the evaluation carried out on social studies learning. The results of the analysis show that social studies education in Indonesia and America has a different history of development, if in Indonesia it developed because of the G30/SPKI rebellion while in America it developed because of the civil war due to multiethnicity in the country. Social studies material in Indonesia is developed in an integrated manner with other subjects taught at the elementary school level, while social studies in America is theme-based. The development of social studies material in Indonesia and America was both developed with the standard 10 themes set by the NCSS. The general assessment of the social studies assessment in both Indonesia and America emphasizes three areas of competence, namely cognitive, affective and psychomotor competencies.